Integration of Augmented Reality Technology in Moral Learning in Islamic Religious Education - Heriady Heriady (International Journal of Language and Ubiquitous Learning, 2024)
Background. The advancement of digital technology requires the world of education to innovate in learning methods, including in the field of Islamic Religious Education (PAI) which teaches moral values. Moral learning, which is often abstract, requires an approach that can effectively improve students' understanding and internalization. The integration of Augmented Reality (AR) technology in moral learning is considered to be able to answer this challenge by presenting a more interactive and contextual learning experience, relevant to the learning style of the current digital generation. Purpose. This study aims to evaluate the effectiveness of the use of AR in moral learning in PAI, especially in improving students' understanding and practice of moral values. The main focus of the research is to see the extent to which AR technology can contribute to building a deep and practical understanding of moral concepts. Method. The study used an experimental design with a quantitative approach, involving 100 junior high school students who were divided into an experimental group and a control group. The research instruments include moral comprehension tests, attitude questionnaires, and qualitative interviews to explore students' learning experiences while using AR technology. The data were analyzed using descriptive and inferential statistics. Results. The results showed that students who studied with AR experienced a significant increase in understanding and internalizing moral values compared to the control group. Students in the experimental group had higher comprehension and engagement scores, which showed the effectiveness of AR in moral learning. AR technology has succeeded in contextualizing moral learning with in-depth and applicative interactive simulations. Conclusion. The conclusion of this study confirms that AR can be an effective tool in moral learning in PAI. AR integration offers a relevant and applicable approach, allowing students to understand and practice moral values in a deeper way.